Metode Life Cycle Assessment Untuk Kajian Dampak Lingkungan Pada Instalasi Pengolahan Air Bersih - Muhammad Purnama Adji; Munawar Ali (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Water treatment plants (WTPs) are critical to providing clean, safe and compliant drinking water. However, the use of chemicals and electrical energy in the process can have a negative impact on the environment.This study examines the environmental impact of WTPs using Life Cycle Assessment (LCA) methodology and SimaPro software. The study aims to investigate how the process of treating clean water affects the environment and to provide a more environmentally friendly replacement for WTP. SimaPro 9.0 is used in the LCA technique of environmental impact assessment. This includes defining the objectives and parameters of the study, collecting data (Life Cycle Inventory), analysing the results (Life Cycle Impact Assessment) and interpreting the data. According to the results of the analysis, the reservoir and lamella units are the main sources of impacts in the Endpoint Impact category. The impacts produced by the Impact 2002+ and ReCiPe 2016 approaches differed, with ReCiPe 2016 showing stronger impacts in certain categories. This study sheds light on how the WTP's clean water treatment process impacts the environment. Reducing the use of chemicals, increasing energy efficiency and implementing environmentally friendly technologies are some suggestions for improvement.